Virulence plasmids in edema disease: Insights from whole-genome analysis of porcine O139:H1 Shiga toxin-producing Escherichia coli (STEC) strains - Nemati, Ali; Gigliucci, Federica; Morabito, Stefano; Badouei, Mahdi Askari (Frontiers in Cellular and Infection Microbiology, 2025)
This study investigates the plasmid sequences of porcine O139:H1 Shiga toxin-producing Escherichia coli (STEC) responsible for Edema Disease (ED). Whole-genome analysis reveals significant similarities between these strains and known plasmids, notably pW1316-2, which harbors key virulence genes like hemolysin (hlyA, hlyB) and adhesion factors (aidA-I, faeE). These genes contribute to the cytotoxicity and host colonization associated with ED. Additionally, similarities to plasmids from Shigella flexneri 2a highlight potential associations in virulence gene regulation, particularly via the Hha-H-NS complex. The identification of sequences resembling plasmid pB71 raises serious concerns about the emergence of highly pathogenic strains, as it includes tetracycline resistance genes (tetA, tetC, tetR). This research emphasizes the role of plasmid-like sequences in ED pathogenesis, indicating important implications for swine industry management and public health.